International legal status and regime of the exclusive economic zone and the open sea: comparative characteristics - Kravchenko, Nataliia (ScienceRise: Juridical Science, 2020)
The scientific article "international legal status and regime of the exclusive economic zone and the high seas: comparative characteristics" is devoted to the study of the general understanding of the categories "exclusive economic zone", "high seas", as well as the definition of the international legal status and regime of the exclusive economic zone and the high seas, including for Ukraine as a maritime power, participating in activities for the use of the World Ocean. It is noted, that according to its legal status, the exclusive economic zone is an international territory and part of the high seas. Freedoms of the high seas are exercised within the exclusive economic zone, taking into account the peculiarities of its regime. Attention is focused on the fact that the international legal regime of the exclusive economic zone is determined by the special rights and obligations of the coastal state, as well as by certain rights of states that are landlocked or in a geographically disadvantaged position, which gives grounds to characterize the legal regime of the exclusive economic zone as a «sui generis». It is noticed, that the use of the territory of the high seas is determined by international law, that is, the high seas belongs to the international legal regime, is determined by the principle of freedom of the high seas and, by its status, is an international territory, not subject to national appropriation. It is emphasized, that the open sea includes a sea space with a specific legal regime (sui generis) - an exclusive economic zone, where the coastal state has separate rights and jurisdictions on the basis of international law. According to its status, the exclusive economic zone is part of the high seas, but the regime of the high seas in the exclusive economic zone is limited in terms of two freedoms - fishing and scientific research. In addition, the purpose of this scientific study, according to its results, is to highlight certain generalizations, definitions and conclusions, aimed at further processing the theoretical and practical problems of the indicated topic; in law-making activities; for teaching legal disciplines, writing textbooks, manuals, courses of lectures, teaching materials